Numerical study on the performance of shell footing - Kim Huat, Bujang; Mohammed, Thamer Ahmed; Al Raziqi, Adel Ahmad (Construction Research Institute of Malaysia, 2008)
This paper describes a study on the performance of shell footings using a non-linear finite element analysis with a finite element code, PLAXIS. The shell footing is found to have a better load carrying capacity compared with the conventional slab (flat) footing of similar cross sectional area. The FE analysis also showed a reasonably good agreement with the laboratory experimental results. The effect of increasing the embedment ratio is also studied and found to increase the load carrying capacity of the shell footings.